"Seu projeto no museu”: recurso para facilitar o acesso de docentes da rede municipal de Belo Horizonte ao projeto circuito de museus - Fabiene Cristina Alexandre de Carvalho (2024)
The purpose of this work was to develop and present the production process of an Ebook aimed at supporting teachers who intend to participate in the “Museum Circuit” project by SMED/PBH (Belo Horizonte Municipal Department of Education). The “Museum Circuit” aims to promote interaction between the school public and museum and cultural spaces in the city of Belo Horizonte. The objective of this research was to build an educational resource that gives visibility and also forms part of the extension course “School Visits to Museums”, aimed at expanding access and valuing educational practices that are based on cultural inclusion and belonging to the city. During the research, we identified the need to support teachers in preparing a project to be submitted to compete for the PBH (Belo Horizonte City Hall) “Museum Circuit” project. The methodology used in this investigation is a qualitative approach, with data collection and analysis procedures from semi-structured interviews with those involved in the preparation and participation of the “School Visits to Museums” Course and course teachers. The Ebook was created based on the application of tools and concepts from the field of design and immersion in the research field, in meetings with the team that idealized and conducted two versions of the “School Visits to Museums” course (in 2022 and 2023). We apply design tools/concepts, such as Legibility, visibility and proximity; the Gestalt Laws; Briefing; Personas; Semantic panel; Models and Prototypes for adapting and using the knowledge and efforts of the teams involved in the actions of the “Museum Circuit” project. In the theoretical framework, we highlight liberating and dialogic education in the context of non formal and museum education, according to Paulo Freire (2011), which is also referenced in the foundation and elaboration of the PNEM National Museum Education Policy. It is expected that the resource produced can facilitate the participation and training of teachers, in order to cooperate in the development of the project to compete for the notice and in the subsequent planning of their practices, valuing and encouraging visits to museum spaces as much as possible, as well as exchange of experiences between teachers, promoting accessibility and democratization of heritage assets that portray our culture.